Alterations in intercellular adhesion molecule 1 (ICAM-1) and vascular cell adhesion molecule 1 (VCAM-1) in human endothelial cells. (October 2018) - Habas, Khaled; Shang, Lijun
Highlights: Exposure of HUVECs to H2 O2 resulted in an increase of ICAM-1 and VCAM-1 mRNA and protein levels. Exposure of the HUVECs to H2 O2 produced significant increases in superoxide anions. The antioxidant NAC attenuated H2 O2 -induced mRNA ICAM-1 and VCAM-1 level and superoxide anions. NAC may protect against atherosclerosis via preventing H2 O2 induced injury to endothelial cells. Abstract: Alterations of Endothelial cells (ECs) play a critical role in different pathogenesis of many serious human diseases, and dysfunction of the vascular endothelium is an indicator for human disorders. Endothelial dysfunction is considered to be an early indicator for atherosclerosis, which is characterised by overexpression of adhesion molecules, including intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1). Hydrogen peroxide (H2 O2 ) released via neutrophils is an important mediator of endothelial cell function. Ambient production of superoxide anion (O2 − ) and subsequently H2 O2 at low levels is critical for regulating endothelial cell functions and proliferation. In this study, we investigated the effects of H2 O2 on the expression of adhesion molecules VCAM-1 and ICAM-1 in cultured human umbilical vein endothelial cells (HUVECs). Intracellular superoxide anion production was detected by using p-Nitro Blue Tetrazolium (NBT) assay. Our results showed that administration of 100μM of H2 O2 on HUVECs for 2, 6, 12 and 24 h induced a time-dependent increase in ICAM-1 and VCAM-1 mRNA and protein expression levels with a significant increase observed from 6 h. HUVECs exposed to H2 O2 exhibit increased O2 −, suggesting that H2 O2 induced oxidative stress may be a reasonable for atherosclerosis. This increase can be reduced by the flavonoid, N-acetyl cysteine (NAC). The modulation of endothelial cell function through this mechanism may underlie the contribution of H2 O2 to the development of vascular disease.